Mesoporous PdBi nanocages for enhanced electrocatalytic performances by all-direction accessibility and steric site activation. Issue 13 (10th March 2022) - Du, Dawei; Geng, Qinghong; Ma, Lian; Ren, Siyu; Li, Jun-Xuan; Dong, Weikang; Hua, Qingfeng; Fan, Longlong; Shao, Ruiwen; Wang, Xiaoming; Li, Cuiling; Yamauchi, Yusuke
Abstract : An effective yet simple approach was developed to synthesize mesoporous PdBi nanocages for electrochemical applications. Abstract : An effective yet simple approach was developed to synthesize mesoporous PdBi nanocages for electrochemical applications. This technique relies on the subtle utilization of the hydrolysis of a metal salt to generate precipitate cores in situ as templates for navigating the growth of mesoporous shells with the assistance of polymeric micelles. The mesoporous PdBi nanocages are then obtained by excavating vulnerable cores and regulating the crystals of mesoporous metallic skeletons. The resultant mesoporous PdBi nanocages exhibited excellent electrocatalytic performance toward the ethanol oxidation reaction with a mass activity of 3.56 A mg −1 _Pd, specific activity of 17.82 mA cm −2 and faradaic efficiency of up to 55.69% for C1 products.